Correlating Color and The Chemical Profiles of Sterculia quadrifida Barks for Herbal Raw Materials Quality - Hertiani, Triana; Siswandi, Siswandi; Pratiwi, Agrita Eka; Pamungkas, Aryaningtyas Widya; Rumondang, Amanda; Rodiata, Tsania Andaya; Pratiwi, Sekar Ayu; Lay, Caterina Siskadewi; Agustina, Ikra (Majalah Obat Tradisional, 2025)
The traditional use of faloak (Sterculia quadrifida R. Br.) stem bark as an effective treatment for various diseases has led to its widespread cultivation and collection. Therefore, this study aims to determine the correlation between the intensity and color variation of faloak stem bark with its antioxidant activity and phytochemical content using chemometrics analysis. The study procedures were carried out by collecting samples from different locations in East Nusa Tenggara, Indonesia. Stem bark intensity and color variations were then associated with chemical profiles of extract produced. Chemical profiles analyzed were Total Phenolic Content (TPC), Total Flavonoid Content (TFC), and antioxidant activity as measured using the DPPH, b-carotene bleaching, and CUPRAC methods. Subsequently, the data were subjected to multivariate statistical analyses utilizing Principal Component Analysis (PCA) and Cluster Analysis (CA). The results showed that color variations on faloak stem bark had no significant impact on cluster formation. CA and PCA showed grouping according to gray value representing color intensity. Meanwhile, PCA revealed significant correlations between gray value of faloak stem bark extract and TPC, antioxidant activity, and extract yield, with TFC having no association. Based on these results, color detection system could be developed to facilitate S. quadrafida bark collection as herbal medicine raw materials in the field.